Complement activation in patients with neuromyelitis optica. - Nytrova, P; Potlukova, E; Kemlink, D; Woodhall, M; Horakova, D; Waters, P; Havrdova, E; Zivorova, D; Vincent, A; Trendelenburg, M (2014)
The role of complement has been demonstrated in experimental models of neuromyelitis optica (NMO), however, only few studies have analysed complement components longitudinally in NMO patients. We measured serum or plasma concentrations of anti-C1q antibodies and complement split products C3a and C4a and soluble C5b-9 in patients with NMO, multiple sclerosis and healthy controls. NMO patients had higher levels of C3a and anti-C1q antibodies than healthy controls. C3a levels correlated with disease activity, neurological disability and aquaporin-4 IgG in NMO patients suggesting a role of the alternative pathway of complement in the pathogenesis of NMO and supporting the strategy of therapeutic complement inhibition.